Analisis Penggunaan Singkatan dan Kata Kiasan Ragam Bahasa Gaul di Media Instagram sejak Pandemi Covid-19 hingga Pascapandemi (Kajian Sosiolinguistik) - Mila, Zarmila; Lubis, Winaria; Suhardjono, Dadi Waras (Jurnal Bahastra, 2024)
The research aims to analyze the use of various uses of slang on the social media Instagram, with a focus on sociolinguistic studies related to the meaning of abbreviations and figurative meanings of slang. This research uses a qualitative descriptive method, namely explaining qualitatively how abbreviations and figurative meanings are used on Instagram social media from the Covid-19 pandemic to post-pandemic. Research data was collected through observation and collecting text from Instagram posts and comments. The research results showed that there were 53 data, including 16 abbreviated meanings, 37 figurative meanings of slang on the social media Instagram. Thus, the use of slang can be useful as a documentary record of linguistic development which adds insight into sociolinguistic studies.